Integrasi Flash Card Pada Literasi Tanaman Obat untuk Peningkatan Agrowisata Kesuma Bangsa - Ardhy, Ferly; Sari, Selly Puspita; Dwiningrum, Riza; Saputri, Silvia Dwi; Hartono, Bayu (Penerbit Goodwood, 2025)
Purpose: The Community Service activity aims to enhance the literacy of Family Medicinal Plants (TOGA) as well as strengthen the potential for sustainable business in the Herbal Agriculture Tourism of Kesuma Bangsa in Pujorahayu Village. The innovation implemented is the development of interactive flash card-based digital education media named Si Toga. This media is equipped with a QR code that connects directly to a mobile web, containing complete information about plant types, benefits, as well as features for online sales of TOGA products. Methodology/approach: The implementation method of activity consists of six stages, namely: (1) planning, (2) implementation, (3) application of technology and innovation, (4) concrete stages in addressing partner issues, (5) partner participation, and (6) program evaluation, (7) sustainability plan. Results/findings: The results of the activities show that the implementation of Si Toga has successfully increased the participants' understanding of TOGA literacy and digital access skills by 90%, which was previously only 50%. Additionally, the digital sales feature also supports the increase in direct transactions of herbal products through the mobile web platform. Conclutions: The integration of digital flash cards through Si Toga has proven effective in supporting education and the sustainable empowerment of TOGA businesses in the agrotourism area. Limitations: This activity is only carried out at the Herbal Plant Agro-tourism of Kesuma Bangsa, Pujorahayu Village. Contribution: This activity contributes to partners in implementing digital herbal plant family literacy innovations, which will ultimately enhance sustainable efforts.